Praktik Pengalaman Lapangan (PPL) Mahasiswa IAIN Madura: Teknik dan Strategi Pengelolaan Kelas Praktik Platform Merdeka Belajar - Alatas, Mochamad Arifin; Romadhon, Sahrul; Efendi, Agik Nur; Zahroh, Farichatuz (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
Teaching and learning activities require classroom management techniques and strategies to run effectively and efficiently. This study aims to describe the techniques and strategies for classroom management for students of Field Experience Practice (PPL) with the independent learning platform of IAIN Madura. This research is descriptive qualitative type. The data in this study are descriptive, reflective, field notes, and documentation. The data source for this research is the interaction of tutors, PPL teachers, and students in teaching and learning activities. The research data were analyzed using the Miles and Huberman model. The results showed that the classroom management technique in the opening activity was a preventive technique. While the core learning activities are preventive techniques and curative techniques. Then in closing activities using preventive techniques. Classroom management strategies in opening activities include asking strategies, feedback strategies, and also group learning strategies. In the core activities, they are also not much different, namely the strategy of asking, feedback, and also the strategy of the group. Meanwhile, the closing activity is a summary, reflection, and no follow-up.